Conflict Resolution Discourse of Green Letter in Surabaya - Nur Azizah Hidayat; Iman Zukhrufi Nur Azzam (Faculty of Law, Universitas Jenderal Soedirman, 2021)
The Green Letter is one of the phenomenon of Land Law in the Surabaya City, because it creates a conflict of interest relating to rights, obligations and authorities, between the Green Letter holder and the Surabaya City Government. The conflict of interest results in injustice and legal uncertainity, for the parties of the conflict. This research aims to provide a conflict of interest resolution discourse on the existence of the Green Letter in the Surabaya City. This research is a doctrinal legal research with historical, statute, and conceptual approaches, as well as non-doctrinal legal research, with a socio-legal approach. In this study, it was found that the positive and negative impacts of Green Letter on the parties to the conflict, could be resolved by deliberation to reach consensus.Keywords: Conflict Resolution; Green Letter; Surabaya